Parking Guidance System Using Wireless Sensor Networks - Rasheed, K. (Institute of Electrical and Electronics Engineers Inc., 2021)
The study's goal is to create a smart parking system using wireless sensor networks (WSNs), which are now being used in almost every field for a variety of applications, including monitoring marine life in oceans, health monitoring, object inspection, smart homes sensor based systems, and the automotive and locomotive industries. The wireless sensor network is built on the basis of a vehicle parking system utilizing the Xbee module after a thorough examination of several systems. The Xbee modules are set up in a star network, with the first node acting as a receiving and transmitter node, and the remaining nodes acting as transmitters. Multiple access time division was utilized in this project. The data is sent by the transmitter node after a predetermined time interval, and it is received by the receiver node without any data collision between two transmitting nodes. Each node's central processing unit is an Arduino. The HC-06 RF module is used to connect wirelessly with the graphical user interface through Bluetooth protocol. The main idea is to build a parking system that is completely wireless and does not rely on a wired network. The WSN-based auto parking system is chosen for the implementation. Â© 2021 IEEE.